Innovation in isolation: diffusion of local foods purchasing and online shopping methods during the pandemic - Yang, Cheng-Xian; Baker, Lauri M.; Mattox, Anissa M.; Peterson, Hikaru H. (Frontiers in Sustainable Food Systems, 2024)
The COVID-19 pandemic caused mainstream food supply chain disruptions, increased food security concerns, and impacted agri-food production and distribution systems. Short food supply chains provided consumers with an alternative method to acquire food outside conventional food supply chains. In this paper, innovation was seen as a solution to external challenges or problems in global food supply chains during a pandemic crisis. The solution was analyzed in the context of the United States and changes in the consumers' behavior and purchasing patterns in the direction of more accepting short supply chains, which led to the successful overcoming of crisis or adaptation of consumers to crisis circumstances. The Diffusion of Innovations was selected as the theoretical framework. Data were collected from 1,002 American adults from July 13 to August 18, 2021, through an online survey. Results showed that consumers with higher educational attainment and financial status, from non-rural areas, and with more conservative viewpoints had higher innovation adoption levels, and they were more likely to embrace short food supply chains as an alternative during disruptions to conventional supply chains. Recommendations provide strategies to increase the use of short supply chains during the crisis to better meet the needs of consumers in the food system and improve marketing and communication efforts. Marketing and communication initiatives should engage these food innovators as opinion leaders to increase the adoption of short food supply chains to stabilize food supply in preparation for future crises.